Comparison of aortic annulus dimensions after aortic valve neocuspidization with those of normal aortic valve using transthoracic echocardiography. (3rd May 2018) - Iida, Yasunori; Akiyama, Sho; Shimura, Kazuma; Fujii, Susumu; Hashimoto, Chihiro; Mizuuchi, Saki; Arizuka, Yumi; Nishioka, Miyuki; Shimura, Nami; Moriyama, Sachiko; Shimizu, Hideyuki; Sawa, Shigeharu
Abstract: OBJECTIVES: This study aimed to elucidate the physiological feasibility of aortic valve neocuspidization (AVNeo) by comparing the aortic annulus dimensions between patients after AVNeo and patients with normal aortic valves. METHODS: From December 2010 to October 2017, we performed AVNeo for various aortic valve pathologies in 147 patients. Of these patients, the aortic annulus dimensions were measured in 25 patients who underwent AVNeo for aortic valve disease as follow-up examination and compared with those measured in 15 patients who had normal aortic valves. Measurements were recorded using electrocardiography-gated transthoracic echocardiography. RESULTS: No significant differences in the aortic annulus dimensions were observed between the patients who had undergone AVNeo and those who had normal aortic valves. In a cardiac cycle, the annulus area in the systolic phase was consistently larger than that in the diastolic phase, which was a physiological condition. CONCLUSIONS: The movement of the aortic annulus after AVNeo is comparable with that of the aortic annulus of a normal aortic valve. Thus, AVNeo can be regarded as a more physiological operation in that it maintains the characteristics of the aortic valve similar to those of a normal aortic valve.